2012
DOI: 10.1111/j.1749-6632.2012.06564.x
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cells are regulated by Cripto, as an intermediary of HIF‐1α in the hypoxic bone marrow niche

Abstract: Cripto has been known as an embryonic stem (ES)- or tumor-related soluble/cell membrane protein. In this study, we demonstrated that Cripto has a role as an important regulatory factor for hematopoietic stem cells (HSCs). Recombinant Cripto sustained the reconstitution ability of HSCs in vitro. Flow cytometry analysis uncovered that GRP78, one of the candidate receptors for Cripto, was expressed on a subset of HSCs and could distinguish dormant/myeloid-biased HSCs and active/lymphoid-biased HSCs. Cripto is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
(137 reference statements)
2
17
0
Order By: Relevance
“…These findings raise an intriguing possibility that cells matured in BM niches may be highly susceptible to aberrant increases in ROS. In support, disruption of ROS homeostasis has been shown to impede the quiescence of hematopoietic stem cells, a paradigm corroborated by our current investigations [21, 37, 38]. Alongside the current research, another recent publication showed that IEX-1 was a key to up regulate NF-kB and to activate Erk signaling resulting in repairing DNA breaks induced by gamma-irradiation in hematopoietic stem cells [39].…”
Section: Discussionsupporting
confidence: 85%
“…These findings raise an intriguing possibility that cells matured in BM niches may be highly susceptible to aberrant increases in ROS. In support, disruption of ROS homeostasis has been shown to impede the quiescence of hematopoietic stem cells, a paradigm corroborated by our current investigations [21, 37, 38]. Alongside the current research, another recent publication showed that IEX-1 was a key to up regulate NF-kB and to activate Erk signaling resulting in repairing DNA breaks induced by gamma-irradiation in hematopoietic stem cells [39].…”
Section: Discussionsupporting
confidence: 85%
“…Researchers have also identified extracellular factors that regulate HIF1α activity in HSCs 52,53 . The soluble protein CRIPTO (also known as TDGF1), and its cell surface receptor 78 kDa glucose-regulated protein (GRP78), have crucial roles in promoting quiescence and in the maintenance of HSCs 52 .…”
Section: Glycolysis and The Hypoxic Nichementioning
confidence: 99%
“…53 The hypoxic microenvironment in the endosteum is a major factor in the integration of skeletal and haematopoietic functions, owing in part to the central role of hypoxia-inducible factor (HIF)-1α in HSC differentiation. 54,55 …”
Section: Biochemistry Of the Nichementioning
confidence: 99%